MAQASID AL-SHARIA IN THE DISTRIBUTION OF PROPERTY - Al-Ayyubi, Solahuddin; Harnidar, Evania (Institut Agama Islam Negeri (IAIN) Bone, 2023)
There is a prohibition of rotating property on people (Q.S. 59:7) so that the discussion of sharia maqasid on distribution becomes essential to research. This paper aims to know the definition and function of the maqasid of shari'ah in concluding the law. Second, to understand the thoughts of scholars towards maqasid shari'ah. Third, to know the implementation of the shari'ah maqasid on the distribution of property. This article uses a qualitative approach. This article is library research. The results showed that sharia maqasid is an important concept in the study of Islamic lawÂ by paying attention in maintaining faith (din), soul (nafs), mind ('aql), progeny (nasl) and wealth (maal) for humankind. Thoughts of scholars toward sharia maqasid were the main goal (universal value) to be achieved from legal provisions both in general and in particular. Sharia maqasid on the distribution of property creates a turnover of wealth among humans fairly and evenly. Distribution of property can be done through various means including nafaqah, zakat, inheritance, will, waqf, infak, alms, qardul Hasan, feeding the poor, qurban, aqiqah, helping others, fulfilling the rights of neighbours, fulfilling guest rights and Profit, and Loss Sharing (PLS), in addition, the distribution of property can also be done through the delivery of state property to citizens who are considered in need.